Association between nonalcoholic fatty liver disease and increased glucose-to-albumin ratio in adults without diabetes - Wang, Shuai; Lin, Xiaohong; Zhu, Chuchen; Dong, Yuqi; Guo, Yiwen; Xie, Zhonghao; He, Xiaoshun; Ju, Weiqiang; Chen, Maogen (Frontiers in Endocrinology, 2024)
Background ： Non-alcoholic fatty liver disease (NAFLD) affects around 30% of individuals globally. Both serum glucose and albumin were demonstrated to be potential markers for the development of NAFLD. We hypothesized that the risk of NAFLD may be proportional to the glucose-albumin ratio (GAR). Methods: Based on information from the NHANES 1999-2018, it was determined that GAR was associated with an increased risk of NAFLD and liver fibrosis utilizing weighted multivariable logistic regression. Participants with a fatty liver index (FLI) over 60 were identified with NAFLD, and those with an NFS > 0.676 with evidence of NAFLD were labeled with advanced hepatic fibrosis (AHF). The liver biopsy was utilized to verify the relationship between GAR and FLD in our center cohort. Mendelian Randomization analysis investigated the genetic relationship between GAR and NAFLD.Results: Of 15,534 eligible participants, 36.4.9% of participants were identified as NAFLD without AHF. GAR was positively correlated with the probability of NAFLD following full adjustment for possible variables. (OR = 1.53, 95% CI: 1.39-1.67). It was confirmed that patients with NAFLD and AHF had an inferior prognosis. The relationship between GAR and NFS was favorable (R = 0.46, P < 0.0001) and NAFLD patients with a higher GAR tended to develop poor survival. In our center cohort, the association between GAR and NAFLD was verified. Conclusions: Among participants without diabetes, greater GAR was linked to higher risks of NAFLD. In addition, NAFLD patients with higher GAR tended to develop liver fibrosis and adverse outcomes.